2004
DOI: 10.4314/sajhe.v18i1.25429
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for measuring the quality of student learning in outcomes-based education

Abstract: A Abstract bstractThe most important principles of outcomes-based education (OBE) is that planning, teaching and assessment should focus on helping learners to achieve significant outcomes to high standards. This cannot be achieved without having suitable ways to describe desired learning outcomes and the quality of students' demonstrations of learning. This article outlines a systematic approach to defining outcomes and describing the relationship between learners' responses to assessment items and their leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 6 publications
1
19
0
1
Order By: Relevance
“…Killen and Hattingh (2004) found that use of SOLO taxonomy opens up a dialogue between teachers and students and places a clear focus on quality learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Killen and Hattingh (2004) found that use of SOLO taxonomy opens up a dialogue between teachers and students and places a clear focus on quality learning.…”
Section: Discussionmentioning
confidence: 99%
“…According to Killen and Hattingh (2004) a relational response builds on the multi-structural response by using a previously learnt concept to integrate the ideas.…”
Section: Relational Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…The social work educator should then clarify the skills to be mastered, develop appropriate teaching activities and develop a set of measures for determining whether the skills has been mastered (Larsen, 1980). According to Killen and Hattingh (2004), OBE has four simple principles. These are:…”
Section: Outcomes-based Education: An Overviewmentioning
confidence: 99%